Differences of endogenous polyamines and putative genes associated with paraquat resistance in goosegrass (Eleusine indica L.). - Qiyu Luo; Jiping Wei; Zhaoxia Dong; Xuefeng Shen; Yong Chen (PLoS ONE)
Background Paraquat is one of the most effective herbicides used to control weeds in agricultural management, while the pernicious weed goosegrass (Eleusine indica) has evolved resistance to herbicides, including paraquat. Polyamines provide high-level paraquat resistance in many plants. In the present study, we selected three polyamines, namely, putrescine, spermidine, and spermine, as putative genes to investigate their correlation with paraquat resistance by using paraquat-resistant (R) and paraquat-susceptible (S) goosegrass populations. Results There was no significant difference in the putrescine nor spermine content between the R and S biotypes. However, 30 and 90 min after paraquat treatment, the spermidine concentration was 346.14-fold and 421.04-fold (P < 0.001) higher in the R biotype than in the S biotype, but the spermidine concentration was drastically reduced to a marginal level after 90 min. Since the transcript level of PqE was low while the spermidine concentration showed a transient increase, the PqE gene was likely involved in the synthesis of the paraquat resistance mechanism, regulation of polyamine content, and synthesis of spermidine and spermine. PqTS1, PqTS2, and PqTS3 encode transporter proteins involved in the regulation of paraquat concentration but showed different transcription patterns with synchronous changes in polyamine content. Conclusion Endogenous polyamines (especially spermidine) play a vital role in paraquat resistance in goosegrass. PqE, PqTS1, PqTS2, and PqTS3 were speculated on the relationship between polyamine metabolism and paraquat resistance. To validate the roles of PqE, PqTS1, PqTS2, and PqTS3 in polyamine transport systems, further research is needed.